PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) DALAM PENYELENGGARAAN PEMERINTAHAN DESA LUBUK BETUNG KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU PROVINSI RIAU - Siska Sintya Dewita; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The low capacity of officials BPD is one of the obstacles to the process of understanding the functions held that what is expected by the villagers less goes well, in other words what is expected by the community with the existing situation does not go hand in hand. Village Consultative Body in the village of Lubuk Betung Rokan IV Koto District of Rokan Hulu has not shown that the maximum performance results. This study aims to investigate the implementation of the Village Consultative Body functions in the village of Lubuk Betung and to determine various factors inhibiting the implementation of these functions. The factors inhibiting the implementation of BPD functions are: (1) the factors of employee performance, (2) the factors of cooperation, and (3) training factors. Therefore, the presence of various factors inhibiting the function execution Village Consultative Body (BPD), resulting in the execution of the function can not go well as expected. The theory used is the theory widjaja who said that the Village Consultative Body is an entity that works as follows: (1) establish the rules the village with the village chief, (2) accommodate and channel the aspirations of the community, and (3) supervising the implementation of regulations and decision of the chief. This study uses descriptive qualitative data collection techniques of observation and interviews. The results of this study demonstrate the implementation of the functions of BPD in mind that (1) the function establishes the rules villages have not been fully implemented properly because of a lack of cooperation between BPD with the village chief, in addition to the BPD in the village of Lubuk Betung also still fakum so that no village regulations newly created, (2) the functions and share their aspirations of society has not done well is because often misunderstanding or difference between the community and the board Village Consultative Body in and share their aspirations, and (3) the monitoring function is no supervision by members of Village Consultative Body on the course of implementation of the regulations and a decision by the village itself and the course Budget village due to lack of understanding of the BPD members of this supervisory function.Keywords: execution, function, Village Consultative Body (BPD)